POLA KEMITRAAN PENGEMBANGAN RUMAH SEWA PEKERJA INDUSTRI DIKAWASAN INDUSTRI Studi Kasus : Kawasan Industri MM2100, Cibitung - Mona Anggiani (Universitas Mercu Buana, 2015)
ABSTRACTThe growing up of economic in Indonesia, automatically increase the activity in industrial area. Industrial Town as the location of the factory build cannot be denied that made the total of factories are increasing too. The labors who work in this industrial town were also increasing. The labors’ need a house to stay in and housing is one of they needed. Labors need housing, not just a house to stay but live. In United States and Canada, there is a program for their labors, which stated by George Fallis and Tom Schwartz and many literatures about the housing program for labor. But in Indonesia, there is not much literature about the housing program for the labors. Department of Housing has the regulation for housing for the employees that the salaryis below some amount. The focus of this research is to describe where the labors live, how the labors housing, and why the partnership of rental housing in industrial town could not be build. MM2100 is the object to be research because this industrial town has the same typical of industrial town in others area. The method of this research is using qualitative methods, by analyzing the benefits and the detriments of supplying labors housing, which supposed to be held by the government, employers, and employees. The conclusion of this research is, that there is still not good communication between the public sector and private sector to supplying the labors housing. As long as there is no communication between those parties, the partnership of labors housing will be not applicable, as what George Fallis said, the non-profit housing will be not working if there is no good perception among parties.Keyword : rental housing, labor, industrial estate, employee housing.ABSTRAKPertumbuhan ekonomi di Indonesia, membuat kegiatan industri pun meningkat. Kawasan Industri sebagai lokasi tempat berdirinya pabrik (sebagai tempat berproduksi), secara terus menerus bertambah jumlah investornya. Jumlah pekerja yang ada di lokasi pun meningkat. Pekerja-pekerja tersebut memerlukan tempat untuk tinggal. Perumahan merupakan satu kebutuhan penting bagi semua orang, termasuk para pekerja industri di sini. Jumlah pekerja industri di Kawasan Industri yang cukup banyak, menuntut keberadan perumahan. Di Amerika Serikat, terdapat program bantuan perumahan bagi pekerja melalui kemitraan yang dikemukakan oleh George Fallis dan Tom Schwartz. Namun di negara Indonesia, belum terdapat program khusus yang serupa. Masih berupa kebijakan, Keputusan Menteri Perumahan Rakyat mengenai subsidi bagi masyarakat yang berpenghasilan sesuai UMR saja. Program kemitraan dalam pengadaan asrama bagi pekerja industri belum dapat berjalan. Penelitian ini dilakukan untuk mengetahui mengapa perumahan bagi pekerja industri di Kawasan Industri MM2100, Cibitung, Bekasi belum dapat terlaksana atau terbangun hingga saat ini. Lokasi pemilihan KI MM2100 karena KI tersebut dapat mewakili tipikal KI lainnya yang ada di daerah Bekasi. Metode analisis yang digunakan adalah dengan melihat keuntungan dan kerugian yang masing-masing pihak yang terkait dengan sistem pengadaan perumahan bagi pekerja industri di KI. Hasil penelitian menunjukkan bahwa perlu adanya persamaan pemahaman di setiap pihak terkait keuntungan, kerugian dan manfaat yang bisa diperoleh apabila perumahan sewa bagi pekerja industri terbangun. Selama semua pihak terkait belum menyamakan persepsi, maka program kemitraan pengadaan perumahan bagi pekerja di kawasan industri tidak terlaksana.Kata kunci : rumah sewa, pekerja pabrik, kawasan industri, perumahan karyawan.